2017
DOI: 10.1364/ol.42.001946
|View full text |Cite
|
Sign up to set email alerts
|

Direct stabilization of optomechanical oscillators

Abstract: We demonstrate a simple and effective technique for stabilizing the oscillation amplitude of a radiation pressure driven RF optomechanical oscillator (OMO). By controlling the optomechanical gain through a feedback loop that uses the oscillation amplitude itself as the feedback parameter, we have been able to suppress the amplitude fluctuations and drift. In contrast to more complex techniques that only lock the relative wavelength detuning, the proposed technique isolates the oscillation amplitude not only fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…We have shown that, using a simple PID controller to drive the NEMS actuator, we can improve the cavity stability by a factor of 7.21 ± 0.02 in comparison to the unlocked optical cavity. For this demonstration, we used the cavity transmission as the input to the PID controller, but alternative feedback signals, such as the oscillation amplitude in the mechanical mode of interest 24 , are also compatible with this technique.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that, using a simple PID controller to drive the NEMS actuator, we can improve the cavity stability by a factor of 7.21 ± 0.02 in comparison to the unlocked optical cavity. For this demonstration, we used the cavity transmission as the input to the PID controller, but alternative feedback signals, such as the oscillation amplitude in the mechanical mode of interest 24 , are also compatible with this technique.…”
Section: Discussionmentioning
confidence: 99%
“…The incident optical field pumps a Brillouin-active medium through electrostriction, which normally generates and amplifies a counter-propagating (i.e., backwardpropagating) Stokes field down-shifted relative to the incident "pump" field's frequency [1,2]. Whilst SBS can be utilized as an amplifying mechanism for Brillouin lasers, it can also degrade the performance of fiber laser sources, severely limiting their power-scaling [3][4][5][6]. It is especially detrimental for pump linewidths narrower than the Brillouin gain bandwidth of a few tens of MHz, including so-called single-frequency light.…”
Section: Introductionmentioning
confidence: 99%
“…It is especially detrimental for pump linewidths narrower than the Brillouin gain bandwidth of a few tens of MHz, including so-called single-frequency light. Therefore, accurate prediction of the power-limit by SBS is of great importance when designing and operating such a system, and thus has been receiving a considerable amount of attention [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…These modes can be selected by adjusting the laser wavelength and coupling strength near optical resonant wavelengths with sufficient quality factor [4,10,14]. For an isolated OMO, fine tuning of each oscillation frequency over a limited range can be achieved by changing the optical power (through optical spring effect) as well as microresonator temperature [14,15]. Alternatively similar to other self-sustained oscillators, the oscillation frequency of OMO can be controlled by injection locking to another oscillator [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%